Edukasi Seksual dalam Pernikahan: Pandangan Syekh At-Tihami dalam Kitab Qurrah Al-Uyun - Affandy, Arif; Ardiansyah, Ardiansyah; Mutiara, Dwi Utamika (JURNAL USM LAW REVIEW, 2023)
This research aims to explore the significant role of sexual education in preventing divorce within the context of Islamic marriages. Through the analysis of Syaikh Abu Muhammad At-Tihami’s primary source, "Qurrah al-‘uyūn," and relevant secondary references, this study identifies various guidelines and regulations relevant to sexual relations within Islam. The research findings highlight that appropriate sexual education has substantial potential in maintaining marital stability, given the importance of adhering to prescribed guidelines and prohibitions regarding sexual practices.The research underscores the importance of selecting the right timing for sexual intercourse, choosing a private and secure location to safeguard privacy, following proper etiquettes, and adopting recommended positions during sexual practices. Additionally, the study emphasizes the significance of mutual satisfaction between spouses as a crucial aspect of marital harmony.The research also reveals specific prohibitions, such as refraining from sexual relations during the wife’s menstruation and postpartum period, avoiding anal intercourse, and abstaining from sexual activities during discouraged times, such as the night of Eid al-Adha, the first night of marriage, mid-month, and the end of each lunar month. This research contributes significantly to a deeper understanding of sexual practices within Islam and underscores the necessity of accurate sexual education in preventing conflicts and divorce within marital relationships. The novelty of this study lies in the in-depth exploration of Syaikh Abu Muhammad At-Tihami’s perspectives on sexual practices within Islamic marriages, providing valuable insights within the context of Islamic matrimony. Penelitian ini bertujuan untuk menjelajahi peran krusial pendidikan seksual dalam mencegah perceraian dalam konteks pernikahan Islami. Ditenagai oleh urgensi memahami dan menerapkan panduan serta regulasi terkait hubungan seksual dalam Islam, metode penelitian melibatkan analisis mendalam terhadap "Qurrah al-‘uyūn" karya Syaikh Abu Muhammad At-Tihami dan referensi sekunder relevan. Keunikannya terletak pada pengungkapan pandangan Syaikh Abu Muhammad At-Tihami mengenai praktik seksual dalam pernikahan Islami. Hasil penelitian menyoroti bahwa pendidikan seksual yang tepat menjadi kunci stabilitas pernikahan, mempertimbangkan waktu, lokasi, etiket, dan pemilihan posisi yang dianjurkan. Keutamaan kepuasan bersama antara suami dan istri diidentifikasi sebagai elemen kunci dari harmoni pernikahan. Larangan khusus, seperti menahan diri selama menstruasi istri dan masa nifas, menghindari hubungan seks anal, dan menjauhi aktivitas seksual selama waktu-waktu yang tidak disarankan, juga diungkapkan. Penelitian ini memberikan kontribusi signifikan untuk memahami praktik seksual dalam Islam dan menyoroti peran penting pendidikan seksual yang akurat dalam mencegah konflik serta perceraian dalam hubungan pernikahan. Keunikan penelitian ini terletak pada penggabungan pendekatan analitis yang mendalam dengan perspektif Islam, khususnya pandangan Syaikh Abu Muhammad At-Tihami, sehingga memberikan wawasan berharga dalam konteks pernikahan Islami.